Pulmonary Abnormalities in Animal Models Due to Niemann-Pick Type C1 (NPC1) or C2 (NPC2) Disease - Roszell, Blair R. (Public Library of Science, 2013)
Niemann-Pick C (NPC) disease is due to loss of NPC1 or NPC2 protein function that is required for unesterified cholesterol transport from the endosomal/lysosomal compartment. Though lung involvement is a recognized characteristic of Niemann-Pick type C disease, the pathological features are not well understood. We investigated components of the surfactant system in both NPC1 mutant mice and felines and in NPC2 mutant mice near the end of their expected life span. Histological analysis of the NPC mutant mice demonstrated thickened septae and foamy macrophages/leukocytes. At the level of electron microscopy, NPC1-mutant type II cells had uncharacteristically larger lamellar bodies (LB, mean area 2-fold larger), while NPC2-mutant cells had predominantly smaller lamellar bodies (mean area 50% of normal) than wild type. Bronchoalveolar lavage from NPC1 and NPC2 mutant mice had an approx. 4-fold and 2.5-fold enrichment in phospholipid, respectively, and an approx. 9-fold and 35-fold enrichment in cholesterol, consistent with alveolar lipidosis. Phospholipid and cholesterol also were elevated in type II cell LBs and lung tissue while phospholipid degradation was reduced. Enrichment of surfactant protein-A in the lung and surfactant of the mutant mice was found. Immunocytochemical results showed that cholesterol accumulated in the LBs of the type II cells isolated from the affected mice. Alveolar macrophages from the NPC1 and NPC2 mutant mice were enlarged compared to those from wild type mice and were enriched in phospholipid and cholesterol. Pulmonary features of NPC1 mutant felines reflected the disease described in NPC1 mutant mice. Thus, with the exception of lamellar body size, the lung phenotype seen in the NPC1 and NPC2 mutant mice were similar. The lack of NPC1 and NPC2 proteins resulted in a disruption of the type II cell surfactant system contributing to pulmonary abnormalities.